Environmentally and Mechanically Stable Selenium 1D/2D Hybrid Structures for Broad-Range Photoresponse from Ultraviolet to Infrared Wavelengths - Chen, Yu-Ze; You, Yen-Ting; Chen, Pin Jung; Li, Dapan; Su, Teng-Yu; Lee, Ling; Shih, Yu-Chuan; Chen, Chia-Wei; Chang, Ching-Chen; Wang, Yi-Chung; Hong, Cheng-You; Wei, Tzu-Chien; et al. (My University, 2018)
Selenium (Se) is one of the potential candidates as photodetector because of its outstanding properties such as high photoconductivity (similar to 8 x 10(4) S cm(-1)), piezoelectricity, thermoelectricity, and nonlinear optical responses. Solution phase synthesis becomes an efficient way to produce Se, but a contamination issue that could deteriorate the electric characteristic of Se should be taken into account. In this work, a facile, controllable approach of synthesizing Se nanowires (NWs)/films via a plasma-assisted growth process was demonstrated at the low substrate temperature of 100 degrees C. The detailed formation mechanisms of nanowires arrays to thin films at different plasma powers were investigated. Moreover, indium (In) layer was used to enhance the adhesive strength with 50% improvement on a SiO2/Si substrate by mechanical interlocking and surface alloying between Se and In layers, indicating great tolerance for mechanical stress for future wearable devices applications. Furthermore, the direct growth of Se NWs/films on a poly(ethylene terephthalate) substrate was demonstrated, exhibiting a visible to broad infrared detection ranges from 405 to 1555 nm with a high on/off ratio of similar to 700 as well as the fast response time less than 25 ms. In addition, the devices exhibited fascinating stability in the atmosphere over one month.
Keywords: Se nanowires arrays; plasma-assisted selenization process; flexible substrate; adhesion ability; broad-ranged photoresponse